A Survey Assessing Kansas Physician Assistants' Attitudes/Beliefs and Current Practices Regarding Implementation of Fall Prevention Strategies in Older Adults - Hale, LaDonna S.; Fraser, Shelton J.; Keuter, Kayla R.; Lee, Felecia A.; Berg, Gina M. (Kansas Journal of Medicine, 2015)
Background. Falls are the leading cause of injury death, nursing home placement, and hospital trauma admissions in older adults. Although guidelines to reduce falls have been available for over a decade, routine implementation by healthcare providers is less than optimal. The purpose of this study was to evaluate the attitudes/beliefs and current practices of Kansas physician assistants (PAs) regarding fall assessment/prevention strategies in older adults and barriers to implementing strategies into daily practice. Methods. A 67-item survey was mailed to all 760 Kansas PAs in 2009; 152 responded. Logistic regressions were performed on current fall prevention practices (exercise, home safety, medications, and vision) to determine attitudes, beliefs, and barriers associated with implementation. Results. Most PAs believe falls are preventable (87%) and implementation of various prevention strategies are their professional responsibility (88% - 96%); yet, less than 50% routinely implement them. Barriers included lack of time (27%), lack of staff (26%), and feeling ill-prepared (18%). Multiple logistic regressions revealed correlations among implementing the medication review strategy and lack of time as well as practicing the exercise strategy and lack of time and awareness of local exercise programs. Conclusions. PAs are aware of the importance of fall prevention, believe falls are preventable, and believe it is their professional responsibility to implement fall prevention strategies with their older adult patients. However, most do not implement strategies in their practice due to a variety of internal and logistical barriers. Fall prevention materials/tools that are practical, simple, inexpensive, and require little implementation time may overcome barriers.